SELECTED INSTITUTIONS AND THE CRIME OF HUMAN TRAFFICKING IN POLAND. INTRODUCTION TO THE ISSUE - Jacek Dworzewski (Zeszyty Naukowe Wyższej Szkoły Finansów i Prawa w Bielsku-Białej)
This paper outlines the role of The Ministry of Justice and the General Prosecutor’s Office which due to legal and doctrinal obligations deal with the issue of combating the crime of human trafficking in Poland. Furthermore, the text provides a focus on the concept of human trafficking in the subject literature as well as legal instruments implemented in combating this form of crime and the characteristics of the Interministerial Committee for Combating and Preventing Trafficking in Human Beings.